China's hukou system and city economic growth: from the aspect of rural–urban migration. Issue 1 (13th November 2019) - Zhang, Kunling; Chen, Chunlai; Ding, Jian; Zhang, Zhinan
Abstract : Purpose: The purpose of this paper is to evaluate the economic impacts of China's hukou system and propose the possible direction for future reform. Design/methodology/approach: The study develops a framework to incorporate the hukou system into the economic growth model. Using prefecture city-level panel data covering 241 cities over the period 2004–2016 and applying the fixed effects and instrumental variable regression techniques, the authors investigated empirically the impacts of the hukou system on city economic growth. Findings: The study provides three main findings. First, the city sector conditionally benefits from labour mobility deregulation that allows migrants to work in cities. Second, the hukou system has different impacts on economic growth among cities with different sizes and administrative levels. Third, to offset the costs of providing exclusive public services to the migrants, the big or high-administrative-level cities can use their high-valued hukou to attract the high-skilled migrants, but the small- or low-administrative-level cities do not have this advantage. Practical implications: This study suggests that the key for further hukou system reform is how to deal with the hukou –welfare binding relationship. Originality/value: The authors developed a theoretical framework and conducted an empirical analysis on the direct relationship between the hukou system and economic growth to reveal the mechanism of how does the hukou system influence the city economic growth and answer the question of why is the hukou system reform so hard in China. The framework also sheds some lights on explaining the success and failure of the hukou system reforms in the past 40 years.